New era of vaccines: new questions - Ortiz-Alfaro, Conrad (2020)
At this moment, the world begins a new era in mass immunization; for this reason, it is important to ask ourselves some questions about vaccines, these powerful tools available today, and for this, we must remember some historical episodes that can help us understand the whole process.